Integrated curriculum in basic and secondary education in Latin America: A systematic review (Papeles, 2026)
Introduction: Integrated curriculum is presented as a necessity for twenty-first-century education. Its development and study have been concentrated mainly in countries such as the United States, Canada, and Spain. In contrast, although it has been implemented in Latin America, gaps in systematization persist, motivating the need to examine its progress in the region. Methodology: A systematic review was conducted in accordance with the Prisma 2020 protocol. The Spider structure and synthesis variables were used to formulate the research question and define eligibility and exclusion criteria. Two thesauri (ERIC and Unesco Thesaurus) were used to conceptually standardize the terms. The documentary searches were carried out using the Scopus, SciELO, and Clacso databases. Results and discussion: The search without inclusion-exclusion criteria yielded 2,410 records. Through automated processes, 2,348 articles were excluded, resulting in a sample of 62 articles at the eligibility stage. Finally, 15 studies were analyzed and reviewed in depth. Five categories are shaping curriculum integration in Latin America. Conclusions: The systematic review indicates that curricular integration in Latin America is a process that is still under development. Its implementation favors meaningful learning, a supportive school environment, and constructive disciplinary dialogue. The need for a solid epistemological and pedagogical foundation, as well as institutional and political support for its advancement, is identified. Promoting an integrated curriculum involves transforming teaching practices, making the curriculum more flexible, and strengthening teacher education.
Keywords: Integrated curriculum; interdisciplinary curriculum; integrated education